Innovative design and delivery of the business capstone course - Fleming, Robert S.; Kowalsky, Michelle (International journal of educational management, 2022)
PurposeThis article discusses the experiences of a university's business school in enhancing the preparation of undergraduates through the innovative design and delivery of Business Policy, the capstone course taken by all business students.Design/methodology/approachThe case discusses the proactive approaches taken to explicitly align efforts between thinking and doing, for both faculty course designers and student participants alike.FindingsTen strategic areas of innovation and improvement are identified and discussed as areas for individual course alignment as well as the impetus for college and university business program development and delivery.Practical implicationsThese innovations can be replicated by other institutions to enhance graduates' career preparation, pursue greater consistency with their organization's mission, develop external stakeholder engagement, and enhance internal collaboration with colleagues within the business school and across the university.Originality/valueThe unique value of this innovative and multifaceted approach was recognized by AACSB International, the elite accrediting agency for business schools, in several articles and at a conference on undergraduate program innovation.